Integrated field control of Dactylopius opuntiae (Cockerell) (Hemiptera: Dactylopiidae) in Opuntia spp. using biorational methods - El Aalaoui, Mohamed; Rammali, Said; Kamal, Fatima Zahra; Ciobica, Alin; Albert, Cristina; Burlui, Vasile; Novac, Bogdan; Bencharki, Bouchaib; Sbaghi, Mohamed (Frontiers in Microbiology, 2025)
IntroductionDactylopius opuntiae (Cockerell) is a major pest affecting Opuntia spp. plantations, causing significant economic losses. The study was conducted at the experimental domain of the National Institute of Agricultural Research, Zemamra, Morocco from 2022 to 2024.ObjectiveThis study aimed to evaluate the efficacy of 19 treatments, including biorational insecticides—mineral oil (MO), black soap (BS), Nicotiana glauca extract (NG)—and the entomopathogenic fungus Alternaria murispora (AM), applied alone or in combinations, with or without pruning, in a randomized complete block design as integrated pest management strategies for D. opuntiae.MethodsTreatments were applied eight times per year at five-week intervals. Data collected included fruit number, cladode number, fruit weight, fruit shape index, phenological phases, infestation level, and visual quality of treated plants.ResultsThe results showed that the combined treatment MO + BS + NG + AM, particularly with pruning, significantly enhanced fruit production (51.1–113.3 across the 3 years), cladode production (26.5–71.4 across the 3 years), fruit weight (188.2–192.7 g across the 3 years), and visual quality of treated plants (visual quality scores: 9.8–10.0 across the 3 years). It also reduced fruit maturation duration (60.9–59.3 days across the 3 years), fruit development period (122.3–117.1 days across the 3 years), and D. opuntiae infestation (scale values: 0.2–0.0 across the 3 years). Pruning played a crucial role in improving the effectiveness of treatments by facilitating coverage and enhancing plant health.ConclusionThis study demonstrates that combining pruning with biological and botanical methods sustainably boosts Opuntia ficus-indica growth and controls D. opuntiae.